Pengaruh Umur Panen dan Level Pupuk Nitrogen Terhadap Produksi dan Kandungan Nutrien Sorghum bicolor L. Varietas Numbu - Dian Astuti; Bambang Suhartanto; Bambang Suwignyo; Melvin Zaenul Asyiqin (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2019)
Sorghum is a potential feed crop to be developed in the tropics that has a long dry season such as in Indonesia. This study aims to determine the effect of harvesting age and nitrogen fertilizer level on the production and nutrient content of sorghum plants Numbu varieties. This study used a split block design with 2 factors and the difference between averages was tested with Duncan's Multiple Range Test (DMRT). The main factors are the age of harvest time consisting of U1 (50 days), U2 (60 days) and U3 (70 days). The second factor is the nitrogen fertilizer level which consists of P1 (0 kg / ha), P2 (100 kg / ha), and P3 (200 kg / ha). Each treatment was carried out 3 replications. The results showed that growth and production were influenced by harvest age and fertilizer level. The nutrient content of sorghum plants of Numbu variety which is influenced by harvest age is only BK, BO and SK, the contents of PK and LK, are not affected by harvest age. The highest BK content in treatment U3 (22.55%). The highest BO content in U3 treatment (91.90%). The highest SK content was in treatment U3 (38.56%). The content of PK and SK was significantly influenced by the nitrogen fertilizer (P <0.05), while the content of BK, BO and LK, was not significantly different. The highest PK content in treatment P3 (7.58%). The lowest SK content was P3 treatment (34.78%). These results indicate that the use of nitrogen fertilizers up to 200 kg / ha can increase (P <0.05) crude protein content, and reduce crude fiber content.